Non formal education in the teaching of peruvian dances among peruvian migrants in Buenos Aires - Benza, Silvia (2009)
The increasing migration of Peruvian citizens to Buenos Aires is a recent phenomenon, and the intensification of the development of organizations and their public presence are correlated with the participation in festivities, civic organizations and the like. This article is a preliminary report on research that focuses on Peruvian dance groups in Buenos Aires and that proposes to describe some of the ways that Peruvian folkdances are transmitted. I show how a process of non formal education is shaped by the interactions among dance groups and between them and representatives of the Peruvian Government in Buenos Aires; and how it is influenced by the need to «demonstrate through performance,» by ways of participating in the groups and by the previous knowledge of the dances that the performers bring with them. The analysis focuses on the microanalytic dimension of representations and practices of the dancers and directors of the dance groups. The fieldwork was carried out in the period 2005-2008 and focused on four groups of Peruvian folk dancers. The phenomena studied are shown to have great potential as intercultural mediators that transcend cultural manifestations to become mechanisms of consciousness raising that reach out to publics beyond the Peruvians themselves.